Synergistic effect of dealumination and ceria impregnation to the catalytic properties of MOR zeolite. (September 2020) - Fajar, A.T.N.; Nurdin, F.A.; Mukti, R.R.; Subagjo,; Rasrendra, C.B.; Kadja, G.T.M.
Abstract: MOR zeolite has been extensively employed as a catalyst in industries. However, high Brønsted acidity in MOR leads to rapid deactivation due to coke deposition on the pore mouths; thus, the surface acidity of MOR needs to be moderated. Herein, we report a modification of MOR chemical composition via acid treatment and deposition of ceria nanoparticles using a wet impregnation method. The acid treatment successfully increases the Si/Al ratio of MOR from 8.39 to 11.58 and reduces the total acid site concentration of MOR from 990 μmol/g to 752 μmol/g. The acidity of MOR is decreased when the Si/Al ratio is increased since the quantity of Brønsted acid sites is proportional to the number of Al framework. In addition, the acid treatment also improves the external surface area of MOR. Furthermore, ceria particles were successfully deposited on the MOR surface using wet impregnation method. The ceria content of parent MOR sample is lower compared to that of preceded by the acid treatment, which may be attributed to the formation of more terminal silanol groups. Finally, catalytic test on Friedel–Crafts alkylation of toluene with benzyl alcohol shows that the synergy between dealumination and the impregnation of ceria significantly improves the activity of MOR zeolite. Graphical abstract: Image 1 Highlights: MOR zeolite is modified using dealumination and Ce impregnation. The resulted MOR has milder acidity and improved textural properties. The activity of MOR is tested on Friedel-Crafts alkylation. The synergy of dealumination and Ce impregnation significantly enhance the activity.